Impact of Stack Parameters on Modeled PM2.5 Conversion Rates: A Case Study of Chungnam during the KORUS-AQ 2016 굴뚝 제원에 따른 PM2.5 전환율 모사 비교: 2016 KORUS-AQ 기간 충남 사례 - Ju, Hyeji; Yoo, Chul; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2019)
Modeled PM2.5 (Particulate Matter of which diameter is 2.5 μm or less) impacts of point source emissions and thus their conversion rates are subject to vary depending on stack parameters as well as its primary and precursor emission rates and other environmental factors. In this study, we compare the modeled impacts of NOx, SO2, NH3, VOC, and Primary PM2.5 (PPM) emissions from major stacks in two large facilities to surface PM2.5 concentrations to illustrate the importance of stack parameters during the estimation. A set of simulations comprised of a control run and emission sensitivity runs were conducted during the period of the 2016 KORUS-AQ (Korea-United States Air Quality). For the comparison, an electric generating utility (EGU) and a non-EGU (NEGU) within a local authority have been selected to assure similar testing environments. Ratios of the modeled conversion rates between two facilities at the local level were 0.1, 3.8, and 0.2 for SO2, NOx, and PPM emissions, respectively, while those ratios at the national level become closer to 1 (0.5, 1.4, and 0.7, respectively). The horizontal gradient of the modeled conversion rates for SO2 and PPM sharply drops near the NEGU due to relatively short-to-medium tall stacks in the facility. In case of NOx emissions, the maximum modeled conversion rates during the simulation period appeared about 70 km downwind of the NEGU. It implies that, in addition to emission rates from point sources, stack parameters should be taken into consideration to develop practical air quality improvement plans, and emission reduction priority may change depending on receptor setup
Keywords: Emission rates; Modeled conversion rate; PM2.5; Point source; Stack parameters